Cooperativas agropecuárias e sua contribuição na formação de jovens sucessores - Brizola, Paola Francine (2022)
Agricultural cooperativism has direct intervention in the production units of associated families and aims to fulfill common objectives, intending to influence the growth and development of rural properties. For this reason, the importance of the segment of agricultural activities and the permanence of young people in the rural environment as successors was understood, since they are fundamental actors in the continuity of cooperatives. Generational succession is understood as a new generation of farmers who remain in the countryside through a gradual process that culminates in the transfer of management and ownership of the property from parents to children. In order to reduce the number of properties without successors, it is necessary that rural organizations encourage the continuation of young people in the countryside through actions. In this sense, the creation of the Rural Cooperative Apprenticeship Program aims to contribute, together with agricultural cooperatives, in encouraging young people to remain on rural properties. Therefore, this study aimed to analyze the Aprendiz Cooperativo do Campo Program regarding its performance in the generational succession in different agricultural cooperatives in the State of Rio Grande do Sul. The methodology that was used is characterized as qualitative and quantitative; A factorial and cluster analysis was carried out, using a questionnaire as a data collection instrument, which was applied through an online form (google forms) and treated in SPSS (Statistical Package for the Social Sciences). The sample of young people participating in the program was given through the promoting agricultural cooperatives and the educational cooperative executing the training, being young people between 14 and 24 years old, with 80% to 100% of the program concluded, aiming to analyze the determinants of the program that contributed to the generational succession of the corresponding properties, totaling 105 young respondents, 54 female and 51 male, distributed in 30 municipalities in the state of Rio Grande do Sul, interviewed in the months of June and July 2022. The results showed that the program has significant importance in the succession process, given that, among the young people interviewed, 78% showed a desire for succession. In the cluster analysis, three groups were obtained; from these, it was considered that the young people who showed greater participation in the activities of the property are the ones who showed the greatest intention of succession, and the young people who showed less intention are the ones who showed less involvement in the activities of the property. The participants evaluated the program positively, demonstrating positive perspectives on all issues presented, claiming greater knowledge about property management, insertion in activities, in addition to greater visualization and training as possible successors. It was concluded, therefore, that the program provokes a stimulus to young people regarding the succession, since these, from the knowledge acquired, felt more able and prepared to continue with the property, given that some who had no intention of succeeding, began to view property as a way of life and work. Therefore, it was possible to affirm that the program has been significant due to the opportunities available to young people and ownership, helping to achieve their objectives, and contributing so that they can become successors.